The Contribution of L-Type Cav1.3 Channels to Retinal Light Responses - Shi, Liheng; Chang, Janet Ya-An; Yu, Fei; Ko, Michael L.; Ko, Gladys Y.-P. (Frontiers in Molecular Neuroscience, 2017)
L-type voltage-gated calcium channels (LTCCs) regulate tonic neurotransmitter release from sensory neurons including retinal photoreceptors. There are three types of LTCCs (Cav1.2, Cav1.3, and Cav1.4) expressed in the retina. While Cav1.2 is expressed in all retinal cells including the Müller glia and neurons, Cav1.3 and Cav1.4 are expressed in the retinal neurons with Cav1.4 exclusively expressed in the photoreceptor synaptic terminals. Mutations in the gene encoding Cav1.4 cause incomplete X-linked congenital stationary night blindness in humans. Even though Cav1.3 is present in the photoreceptor inner segments and the synaptic terminals in various vertebrate species, its role in vision is unclear, since genetic alterations in Cav1.3 are not associated with severe vision impairment in humans or in Cav1.3-null (Cav1.3-/-) mice. However, a failure to regulate Cav1.3 was found in a mouse model of Usher syndrome, the most common cause of combined deafness and blindness in humans, indicating that Cav1.3 may contribute to retinal function. In this report, we combined physiological and morphological data to demonstrate the role of Cav1.3 in retinal physiology and function that has been undervalued thus far. Through ex vivo and in vivo electroretinogram (ERG) recordings and immunohistochemical staining, we found that Cav1.3 plays a role in retinal light responses and synaptic plasticity. Pharmacological inhibition of Cav1.3 decreased ex vivo ERG a- and b-wave amplitudes. In Cav1.3-/- mice, their scotopic ERG a-, b-wave, and oscillatory potential amplitudes were significantly dampened, and implicit times were delayed compared to the wild type (WT). Furthermore, the density of ribbon synapses was reduced in the outer plexiform layer of Cav1.3-/- mice retinas. Hence, Cav1.3 plays a more prominent role in retinal physiology and function than previously reported.